The role of social capital in empowering individuals for sustainable development in Iraq - Alawe Abdullah, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the role of social capital is to empower individuals and achieve sustainable development in the Iraqi society. In light of seeking a strategy that reshapes human behavior according to the standards of sustainable development that prevail in societies today, the problem of the present study is focused on the role of social capital in empowering individuals to gain sustainable development. The significance of the present study is due to the strong need to achieve sustainable development and the participation of all members of the Iraqi society in achieving this goal. Because sustainable societies require a solid foundation of social capital, reform of social, economic, and political modernization cannot achieve goals when there is no moral and ethical framework that supports relationships and mutual interactions and enhances the areas of trust that must be available. Interest in building social capital and its value, moral, and religious components is a way to develop social capital. The present study aims to identify the characteristics and components of social capital to identify the importance of social capital and its functions for achieving sustainable development in the Iraqi society. The present study belongs to descriptive studies. It is based on the social survey method; the sample uses the data collection tool in a questionnaire form.The most important result related to the characteristics of the community of the present study is that there is a diversity of beneficiaries in order to satisfy their needs and develop their capabilities to solve their problems. The results indicate that there is a diversity in the ages of the beneficiaries of income-generating loans. These loans develop social capital at all different stages of life to achieve sustainable development. This confirms that these loans are provided to all members of the Iraqi society without any discrimination.The present study recommends organizing training courses for workers in these loans to provide them with appropriate experiences and skills, benefit from the experiences of others in this field, and raise the competence of workers to develop social capital to achieve sustainable development in the Iraqi society. It is necessary to develop social welfare policies to activate building and developing social capital.